Pathophysiology and prevention of postoperative peritoneal adhesions - Arung, Willy (Baishideng Publishing Group Co., Limited, 2011)
Peritoneal adhesions represent an important clinical challenge in gastrointestinal surgery. Peritoneal adhesions are a consequence of peritoneal irritation by infection or surgical trauma, and may be considered as the pathological part of healing following any peritoneal injury, particularly due to abdominal surgery. The balance between fibrin deposition and degradation is critical in determining normal peritoneal healing or adhesion formation. Postoperative peritoneal adhesions are a major cause of morbidity resulting in multiple complications, many of which may manifest several years after the initial surgical procedure. In addition to acute small bowel obstruction, peritoneal adhesions may cause pelvic or abdominal pain, and infertility. In this paper, the authors reviewed the epidemiology, pathogenesis and various prevention strategies of adhesion formation, using Medline and PubMed search. Several preventive agents against postoperative peritoneal adhesions have been investigated. Their role aims in activating fibrinolysis, hampering coagulation, diminishing the inflammatory response, inhibiting collagen synthesis or creating a barrier between adjacent wound surfaces. Their results are encouraging but most of them are contradictory and achieved mostly in animal model. Until additional findings from future clinical researches, only a meticulous surgery can be recommended to reduce unnecessary morbidity and mortality rates from these untoward effects of surgery. In the current state of knowledge, pre-clinical or clinical studies are still necessary to evaluate the effectiveness of the several proposed prevention strategies of postoperative peritoneal adhesions.